Advice given by NHS Direct in Wales: do deprived patients get more urgent decisions? Study of routine data. Issue 9 (21st July 2017) - Peconi, Julie; Macey, Steven; Rodgers, Sarah; Russell, Ian; Snooks, Helen; Watkins, Alan
Abstract : Background: In the UK, National Health Service Direct Wales (NHSDW) uses computerised decision support software to advise patients on appropriate care. However, the effect of deprivation on the advice given is not known. We aimed to estimate the effect of deprivation on advice given by nurses in NHSDW adjusting for confounding variables. Methods: We included 400 000 calls to NHSDW between January 2002 and June 2004. We used logistic regression to model the effect of deprivation on advice given by nurses in response to calls seeking advice or information. We analysed two outcomes: receiving advice to phone 999 emergency care rather than to seek other care and receiving advice to seek care face to face rather than self-care. Results: After adjustment for covariates, an increase in deprivation from one-fifth of the distribution to the next fifth increased by 13% the probability that those calling for advice rather than information received advice to phone 999 (OR 1.127; 95% CI from 1.113 to 1.143). Deprivation increased the corresponding probability of being advised to seek care face to face rather than self-care by 5% (OR 1.049; 95% CI from 1.041 to 1.058) within advice calls and by 3% (OR 1.034; 95% CI from 1.022 to 1.047) within information calls. Conclusions: Deprivation increased the chance of receiving more urgent advice, particularly advice to call 999. While our dataset may underestimate the 'need' of deprived patients, it yields no evidence of major inequity in advice given to these patients.